WOMAN IMAGE IN LITERARY WORKS - Kurnia Ningsih (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2014)
SOSOK PEREMPUAN DALAM KARYA SASTRAAbstractCurrently, women have started to gain access to the public sphere, which was traditionally reserved for men. However, questions remain whether these women have already gained due recognition for their work in the public domain. This phenomena are also present in literature, a creative work which is believed to be able to depict social phenomena with ample clarity. Three short stories published in the Jakarta Posts 2008, and Kompas 2012 chosen to see the reflection of women who entered the public domain which is strongly patriarchal in nature. Ironically, patriarchy still strongly presents in custom, tradition, and religion in which the sanctity of Eastern culture must be kept at all cost.Keywords: image, woman, literary worksAbstrakSaat ini, perempuan sudah mulai mendapatkan akses ke ruang publik, yang secara tradisional untuk laki-laki. Namun, pertanyaannya tetap apakah wanita ini telah memperoleh pengakuan untuk pekerjaan mereka dalam domain publik. Fenomena ini juga hadir dalam sastra, karya kreatif yang diyakini dapat menggambarkan fenomena sosial dengan cukup jelas. Tiga cerita pendek yang diterbitkan di Jakarta Post 2008, dan Kompas 2012 yang dipilih untuk melihat pantulan wanita yang memasuki domain publik yang sangat patriarkal di alam. Ironisnya, patriarki masih sangat hadir dalam adat, tradisi, dan agama di mana kesucian budaya Timur harus disimpan di semua biaya.Keywords: sosok, perempuan, karya sastra